Viking Games and Sámi Pastimes: Making Balls of Fomitopsis betulina - Svanberg, Ingvar; Lidström, Isak (Ethnobiology Letters, 2019)
Ethnomycology is the study of the bio-cultural aspects of human-fungal interactions. This article discusses the involvement of the bracket fungus Fomitopsis betulina within the material culture of traditional games. With a particular focus on the Nordic countries, the aim is to review and analyze the use of simple balls made of bracket fungi. We argue that the fungi ball can be considered the precursor of the rubber (and the gutta-percha) ball. Moreover, the replacement of fungi balls with rubber balls marks, to a certain extent, a temporal transition from traditional folk games with roots in pre-industrial society to modern sports in which balls and other equipment received a more standardized shape.